2021
DOI: 10.1002/stem.3344
|View full text |Cite
|
Sign up to set email alerts
|

Niche-dependent inhibition of neural stem cell proliferation and oligodendrogenesis is mediated by the presence of myelin basic protein

Abstract: Neural stem and progenitor cells (collectively termed neural precursor cells [NPCs]) are found along the ventricular neuraxis extending from the spinal cord to the forebrain in regionally distinct niches comprised of different cell types, architecture, and cell-cell interactions. An understanding of the factors that regulate NPC behavior is critical for developing therapeutics to repair the injured central nervous system. Herein, we demonstrate that myelin basic protein (MBP), the major cytoplasmic protein con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It remains unanswered why, compared to zebrafish, mammal ependymal cells generate mainly astrocytes, few oligodendrocytes, and no neurons after SCI. This could be due to astrocytic-fate determining factors expressed by these cells prior to injury such as SOX9 or NFIA transcription factors [ 6 ] or by structural proteins in the environment such as myelin basic protein [ 77 ]. In addition and reminiscent of the zebrafish situation [ 78 ], here we found evidence that their fate could be influenced by inflammatory cytokines provided by the environment, possibly microglia.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unanswered why, compared to zebrafish, mammal ependymal cells generate mainly astrocytes, few oligodendrocytes, and no neurons after SCI. This could be due to astrocytic-fate determining factors expressed by these cells prior to injury such as SOX9 or NFIA transcription factors [ 6 ] or by structural proteins in the environment such as myelin basic protein [ 77 ]. In addition and reminiscent of the zebrafish situation [ 78 ], here we found evidence that their fate could be influenced by inflammatory cytokines provided by the environment, possibly microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, neurons are vital for reconstruction of the neural network and proper function. It has been reported that the majority of the endogenous or exogenous NSPCs in the injury site tend to differentiate into glial cells rather than neurons, resulting in limited success in functional recovery. , To solve this issue, various attempts have been made to alleviate the inhibitory microenvironment for improving neuronal differentiation in vivo . , In our previous studies, epidermal growth factor receptor (EGFR) neutralizing antibody was used for Col scaffold functionalization to block EGFR-related signaling triggered by myelin-associated proteins. , The functionalized Col scaffolds improved neuronal differentiation of exogenous NSPCs embedded in the scaffolds and promoted functional recovery of SCI rats. In a follow-up study, we demonstrated that EGFR neutralizing antibody functionalized Col scaffolds induced neurogenesis of endogenous NSPCs, leading to locomotion recovery .…”
Section: Resultsmentioning
confidence: 99%
“…57,58 To solve this issue, various attempts have been made to alleviate the inhibitory microenvironment for improving neuronal differentiation in vivo. 59,60 In our previous studies, epidermal growth factor receptor (EGFR) neutralizing antibody was used for Col scaffold functionalization to block EGFR-related signaling triggered by myelin-associated proteins. 35,61 The functionalized Col scaffolds improved neuronal differentiation of exogenous NSPCs embedded in the scaffolds and promoted functional recovery of SCI rats.…”
Section: Resultsmentioning
confidence: 99%
“…Oligodendrocytes are the myelinating cells in the CNS. While the presence of mature oligodendrocytes has not been demonstrated to directly affect NSC behavior, exposure to oligodendrocyte-associated proteins released following injury/disease has been shown to have profound effects on their behavior [ 48 , 182 ] Following SCI, oligodendrocytes undergo rapid cell death which persists for up to three months post-injury [ 183 ]. One of the most abundant proteins comprising mature is myelin basic protein (MBP).…”
Section: Regulating Neural Precursors To Enhance Neurorepairmentioning
confidence: 99%
“…Normally cytoplasmic is released into the microenvironment following SCI [ 184 ]. Both in vitro and in vivo studies have shown that MBP is inhibitory to NSC proliferation and NSC-derived oligodendrogenesis [ 48 , 182 ]. Most interesting, the observed inhibition is not a direct effect of MBP on NSCs, but instead is due to the indirect effect of MBP on spinal cord PVZ cells, which then release an unidentified factor that acts on NSCs [ 46 , 176 ].…”
Section: Regulating Neural Precursors To Enhance Neurorepairmentioning
confidence: 99%